Impact of CytoSorb and CKRT on hemodynamics in pediatric patients with septic shock: the PedCyto study - Bottari, Gabriella; Guzzo, Isabella; Cappoli, Andrea; Labbadia, Raffaella; Perdichizzi, Salvatore; Serpe, Carmela; Creteur, Jacques; Cecchetti, Corrado; Taccone, Fabio Silvio (Frontiers in Pediatrics, 2023)
Background: There is a lack of data to support the use of hemoadsorption in pediatric septic shock.The aim of our study was to assess the effectiveness and safety of Cytosorb therapy in this setting.Phase II interventional single arm pilot study in which 17 consecutive children admitted with septic shock who required continuous kidney replacement therapy (CKRT) and weighed ≥ 10 kg were included. A CytoSorb (CytoSorbents Inc, New Jersey, USA) hemoadsorption cartridge was added to the CKRT every 24 hours for a maximum of 96 hours. A control group of 13 children with septic shock treated with CKRT but not hemoadsorption at Children's Hospital Bambino Gesù and enrolled in the EuroAKId register was selected as an historical cohort. The primary outcome of the study was a reduction in vasopressor or inotrope dose of > 50% from baseline by the end of Cytosorb therapy. Secondary outcomes included hemodynamic and biological changes, changes in severity scores, and 28-day mortality.Results: There were significant decreases in the Vasoactive Inotropic Score (VIS) and the Pediatric Logistic Organ Dysfunction 2 (PELOD-2) score at 72 and 96 hours from the start of the Cytosorb therapy compared to baseline; the reductions were larger in the hemoadsorption group than in the control group (historical cohort). 28-day mortality was lower, although not significantly, in the hemoadsorption group when compared to the control group (5/17 [29%] vs. 8/13 [61%] OR 0.26 [95% CI 0.05-1.2]; p= 0.08).Conclusions: CytoSorb therapy may have some benefits in pediatric patients with septic shock. Future larger randomized trials are needed in this setting.